Phytochemical profile, antioxidant and cytotoxic potential of Parkinsonia aculeata L. growing in Saudi Arabia - Sahar Abdelaziz; Hanan M. Al Yousef; Ali S. Al-Qahtani; Wafaa H.B. Hassan; Omer I. Fantoukh; May A. El-Sayed (Elsevier, 2020)
Parkinsonia aculeata L. growing in Saudi Arabia was investigated for its phytochemical profile, antioxidant, and cytotoxic properties. UPLC-ESI-MS/MS was employed as a powerful technique for the characterization of secondary metabolites from a hydroalcoholic extract, dichloromethane, and ethyl acetate fractions of P. aculeata L. aerial parts. Sixty-nine compounds (flavonoids, anthocyanins, phenolics and fatty acids) were detected and characterized; flavonoids were the abundant components in the analyzed samples. The dichloromethane fraction was rich in phenolics as vanillic acid hexoside, flavonols as 3,7-dimthylquercetin, and flavones as 3'-hydroxymelanettin. However, the ethyl acetate fraction was rich in flavonoid-C-glycosides as luteolin-8-C-β-D-glucoside (orientin) and apigenin-8-C-glucoside (vitexin), flavonoid- O, C-diglycosides such as luteolin 7-O-[6''-dihydrogalloyl]-glucosyl-8-C-pentosyl-(1 → 2)-glucoside and 2''-O-rhamnosyl isoorientin. These compounds were identified for the first time in dichloromethane and ethyl acetate fractions of Saudi P. aculeata L.Additionally, all the samples were assessed for antioxidant activity using DPPH radical scavenging method and for cytotoxic activity through MTT assay. Accordingly, the most active fraction was the ethyl acetate which showed the highest antioxidant activity (SC50 = 57.4 ± 1.2 μg/mL) compared with the positive control, ascorbic acid (SC50 = 12.4 ± 0.5 μg/mL) and moderate cytotoxicity against HepG-2 (hepatocellular carcinoma) and MCF-7 (breast carcinoma) cell lines with IC50 = 56.9 ± 3.1 and 95.8 ± 3.8 μg/mL, respectively compared with cisplatin (IC50 = 3.67 ± 0.22 and 5.71 ± 0.57 μg/mL, respectively for both cell lines). The antioxidant and cytotoxic activities may be attributed to the presence of high percentage of phenolic compounds and hydroxylated flavonoids detected in ethyl acetate fraction using UPLS-ESI-MS/MS.